Guidance note for gender-inclusive agro-advisories in Vietnam - CGIAR Research Program on Policies, Institutions, and Markets (2020)
The guidance note is based on work in the provinces of Ha Tinh and Dien Bien and has already been piloted in Ha Tinh.